EDGE-NATIVE CABLE ACCESS NETWORK WITH UDP TERMINATION (Computer systems and information technologies, 2025)
This paper introduces a software-defined architectural model for modernizing upstream transport in hybrid fiber-coaxial networks through user-space UDP termination using the VPP HostStack. The approach aims to overcome performance limitations inherent in DOCSIS-based systems by relocating transport-layer processing from centralized cores to multi-access edge computing nodes co-located with Remote PHY Devices. Unlike centralized vCMTS deployments or full-fiber upgrades, this model enables enhanced throughput and session-level concurrency without modifying coaxial infrastructure, DOCSIS PHY signaling, or customer premises equipment. The system is built on FD.io’s Vector Packet Processing framework and validated through CI-integrated benchmarking using the CSIT testbed and iperf3 traffic generator. Test executions were performed on a two-node Intel Ice Lake setup interconnected via 100GE Intel E810CQ interfaces. The benchmarking workflow used iperf3 dynamically linked with libvcl_ldpreload.so, enabling transparent redirection of UDP socket operations to the HostStack without modifying the application code. Two traffic scenarios were evaluated: a baseline with one UDP stream achieving 15.5 Gbps, and a scaled case with one client transmitting ten concurrent streams reaching 28.1 Gbps. The results demonstrate an 81% throughput gain with minimal variance, confirming the HostStack’s efficiency under concurrent flow conditions. Integration via LD_PRELOAD proved stable, transparent, and production-compatible. These findings validate the scalability, reproducibility, and operational viability of edge-based UDP termination for HFC modernization. The proposed model offers a low-disruption upgrade path for cable operators, enabling phased deployment of user-space transport enhancements with CI/CD compatibility, improved upstream utilization, and support for multi-session, latency-sensitive applications such as telemetry, video streaming, and cloud synchronization. In addition, this architecture enables measurable performance improvements without hardware changes, costly rewiring, or disruptions to existing customer services.
Keywords: network performance; software-based packet processing; network scalability; traffic optimization; performance evaluation